Brain MR Imaging in Acute Hyperammonemic Encephalopathy Arising from Late-Onset Ornithine Transcarbamylase Deficiency - Takanashi, Jun-ichi (AJNR Am J Neuroradiol, 2003)
Summary: The brain MR imaging characteristics of three patients with acute hyperammonemic encephalopathy resulting from late-onset ornithine transcarbomylase deficiency are presented. MR images revealed injury to the cortex, especially the cingulate gyrus and insular cortex, with sparing of the perirolandic and occipital cortices. These findings presumably reflect the distribution of brain injury from hypoperfusion secondary to hyperammonemia. Knowledge of the MR findings may help expedite diagnosis and treatment and prevent chronic impairment.